Evaluation of dynamic stability in monitoring control system by the road machines technical-and-economic efficiency - Konstantin P. Mandrovskiy (Advanced Engineering Research)
The study objective is to review the prerequisites for reducing the time of transport movements of the road-building machinery. On the basis of the information received, the corresponding recommendations used in the performance control system and technical audit can be elaborated. Shortcomings of the existing monitoring systems are marked. It is shown that their application to improve the technical-and-economic efficiency of the road vehicles does not allow achieving the controlled results. The technical-and-economic effect should be assessed by the unit cost criterion taking into account the cost for ownership. To calculate such a criterion, it is necessary to have the source information that can be obtained by monitoring. At a minimum criterion, there are work performance and operating quality time limits. The possibility of implementing restrictions on the time performance which largely depends on the machine transportation operations time is considered. Transport operations, in turn, are determined by the stability level, so to elaborate recommendations on reducing the transport operations time it is necessary to evaluate the stability by special calculating formulas. Various options for calculating are considered, the option of differential rocking equations is selected. It is noted that the working process is better described by the loading workflow diagrams, so they should be built on the basis of differential equations. An example of the loading diagram construction for a front loader is given. The application of loading diagrams to elaborate recommendations on reducing the transport operations time is shown